Examining the association between the built environment and active travel using GPS data: A study of a large residential area (Daju) in Shanghai. (January 2023) - Zhang, Surong; Li, Jingwen; Wang, Lan; Kwan, Mei-Po; Chai, Yanwei; Du, Yirui; Zhou, Kaichen; Gu, Hao; Sun, Wenyao
Abstract: Automobile dependence and physical inactivity have become common health challenges for residents in large suburban residential areas. Limited literature has examined the associations between the built environment and active travel in such residential areas and the differences in these associations among residents from different neighborhoods. To avoid inaccurate results potentially derived from residence-based measures, we adopt a mobility-based approach for environmental exposure assessment. Using GPS data from 530 trips made by 98 participants in a large residential area in Shanghai, we investigate the relationships between neighborhood types, pollution perceptions, built environment features and active travel. The results indicate that residents in affordable and relocation housing make fewer active trips than those in market-rate housing, while the built environment seems to mitigate this difference. Sports facilities promote active travel while commercial facilities and road intersections discourage it. We identify significant interactions between the percentage of green space and neighborhood type, as well as floor area ratio and air pollution perception. Interventions promoting active travel include active-travel-friendly design for commercial facilities and road intersections, the provision of more sports facilities, a careful increase in floor area ratio, and the provision of more green space that is attractive to residents from different neighborhoods. Highlights: GPS tracking devices were used to collect individuals' travel routes. Active-travel-friendly design is needed for commercial facilities and intersections. Urban green space fails to promote active travel for residents turned from farmers. Increasing FAR could promote active travel where air pollution perception is slight.